1979
DOI: 10.1080/00222895.1979.10735172
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor Reminiscence as a Function of Sex and Length of Rest Period

Abstract: Sex differences in psychomotor reminiscence were examined as a function of the length of the rest period. Five groups of Caucasian subjects, each group consisting of 12 males and 12 females, practiced continuously for 3 min on a mirror-tracking task, then rested for 0,1, 2, 4, or 8 min before resuming continuous practice. Reminiscence in both sexes increased as negatively accelerated functions of the amount of rest. The asymptotic level of reminiscence was higher for females than for males, but the quadratic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
9
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
4
9
0
Order By: Relevance
“…And, having accumulated more I Rat the onset of rest, they reminisce more across rest. Similar results were found in a mirror tracking task (Huang & Payne, 1975), and the applicability of I R theory to that situation was well supported (McBride & Payne, 1979;McCaffrey & Payne, 1977).…”
supporting
confidence: 85%
“…And, having accumulated more I Rat the onset of rest, they reminisce more across rest. Similar results were found in a mirror tracking task (Huang & Payne, 1975), and the applicability of I R theory to that situation was well supported (McBride & Payne, 1979;McCaffrey & Payne, 1977).…”
supporting
confidence: 85%
“…If this is so, and if the IR concept is fundamentally credible, one must fmd that (1) with the amount of prerest practice held constant, the amount of reminiscence will increase for both sexes as a negatively accelerated function of the length of the rest period, (2) the asymptotic level of this function will be higher for females than for males, and (3) the slope of the prerest performance curve will be less for females than for males. These expectations have been confirmed (McBride & Payne, 1979). On the same hypothesis it was also predicted that the well-known male dominance in rotary pursuit performance would disappear under highly distributed practice conditions.…”
supporting
confidence: 69%
“…On this hypothesis,aselaborated elsewhere (Coppage & Payne, 1981;McBride & Payne, 1979) , females reminisce more than males do because they accumulate more IR per unit of prerest practice. If this is so, and if the IR concept is fundamentally credible, one must fmd that (1) with the amount of prerest practice held constant, the amount of reminiscence will increase for both sexes as a negatively accelerated function of the length of the rest period, (2) the asymptotic level of this function will be higher for females than for males, and (3) the slope of the prerest performance curve will be less for females than for males.…”
mentioning
confidence: 99%
“…With respect to reminiscence in targeting scores, a comparison of Groups 1 and 2 showed that 5 min of rest produced a significant amount of reminiscence, t(73)=4.16, With regard to the sex effect, let it merely be noted in passing that females gained more than males across the 5-min interval between the two segments of mirror tracking, as one would expect from the studies of Huang and Payne (1975) and McBride and Payne (1979). For targeting measures, the means were 3.93 and 8.9 for males and females respectively, and t(72)=3.91, p<.001.…”
Section: Resultsmentioning
confidence: 91%